A new retrofit approach to the absorption-stabilization process for improving energy efficiency in refineries. (1st January 2017) - Liu, X.G.; He, C.; He, C.C.; Chen, J.J.; Zhang, B.J.; Chen, Q.L.
Abstract: In a refining complex, an absorption-stabilization process used in the production of end-use petro-products (i.e. stable gasoline and liquefied petroleum gas) is energy-intensive and costly. A new absorption-stabilization process with a two-stage condensation section is introduced in this work to further improve energy-use performance. In the new process, a condenser, a condensed oil tank, and a side-reboiler are integrated into the original process and then a heat integration scheme is performed. Compared with the existing process, the proposed process can reduce the cold utility and hot utility by 17.98% and 25.65%, respectively, as well as decrease the total annual operating costs of the heat exchanger network by 17.48%. Additionally, the process retrofit reduces the annual operating costs of cooling water and steam by about 346, 617 at the expense of capital costs around 487, 006, and the corresponding payback period is approximately 17 months. Highlights: Energy analysis is proposed for the existing absorption-stabilization process. A new absorption-stabilization process is presented to reduce energy requirement. A side-reboiler is introduced for the heat integration of the new process. HENs are designed and compared between the existing and new processes.